Superior electrochemical performance of non-precious Co-Ni-Mo alloy catalyst-impregnated Sr2FeMoO6-δ as an electrode material for symmetric solid oxide fuel cells. (10th September 2016) - Rath, Manasa K.; Lee, Ki-Tae
Graphical abstract: Highlights: Sr2 FeMoO6-δ (SFM) was synthesized by a sucrose-modified combustion technique. Sr2 FeMoO6-δ is a promising symmetrical electrode material for SSOFC. Nano-sized Co-Ni-Mo was impregnated by a glycine-mediated impregnation. Incorporation of Co-Ni-Mo improves catalytic activity. Activation energy for the HOR was also decreased by the impregnation of Co-Ni-Mo. Abstract: Double perovskite-based Sr2 FeMoO6-δ (SFM), as an electrode material for symmetric solid oxide fuel cells (SOFCs), has been synthesized by a sucrose-modified combustion technique. SFM showed metallic conducting behavior with a conductivity of 215.72 S cm −1 in dry H2 at 800 °C. The polarization resistance (Rp ) for H2 oxidation, evaluated using half-cell symmetry, was recorded as 0.192 Ω cm 2 under humidified H2 at 800 °C. Improved catalytic activity was accomplished by impregnation of Pd or Co-Ni-Mo (0.1:5:1 molar ratio, CNM) via a glycine-mediated impregnation technique. The Rp values for the Pd- and CNM-impregnated SFM were 0.087 and 0.060 Ω cm 2, respectively, under humidified H2 at 800 °C. The symmetric SOFC with an La0.8 Sr0.2 Ga0.8 Mg0.2 O3-δ (LSGM) electrolyte and a CNM-impregnated SFM electrode showed maximum power densities of 1066 mW cm −2 and 480 mW cm −2 at 800 °C under humidified H2 and CH4, respectively.